Mito, guerra y utopía: formas de resistencia indígena en la América colonial - Diana Roselly Pérez Gerardo (Nuevo mundo - Mundos Nuevos, 2021)
This article offers an overview of multiple strategies that can be considered as resistance. It contemplates different kinds of actions: from violent uprisings to daily practices that disrupted the colonial domination along the continent. The aim is to present the wide range of practices, deployed by indigenous people from dissimilar regions, to confront exploitation and dispossession. Different types of insurrection or disobedience are addressed and a distinction is made among the responses to conquest, rebellions against authorities, both in nuclear zones and in borderlands. Within the wide margin of negotiation this paper focuses on other kinds of insurrection, some of which were executed from home, work centers and even religious rituals and allowed indigenous people to lessen the economic burdens, recreate their ancestral repertoires, as well as denounce abuses and demand justice.